Lysosome triggered near-infrared fluorescence imaging of cellular trafficking processes in real time - Marco Grossi (Nature Portfolio, 2016)
Real time cellular fluorescence imaging requires a probe that displays high degrees of localisation, low toxicity and good photostability. Here, the authors report a near infrared fluorophore that displays pH-sensitive fluorescence based on phenol/phenolate interconversion, showing real time imaging of cellular processes.